2015
DOI: 10.1371/journal.pone.0069533
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Bacteria Isolated from Ancient Arctic Soil Exposes Diverse Resistance Mechanisms to Modern Antibiotics

Abstract: Using functional metagenomics to study the resistomes of bacterial communities isolated from different layers of the Canadian high Arctic permafrost, we show that microbial communities harbored diverse resistance mechanisms at least 5,000 years ago. Among bacteria sampled from the ancient layers of a permafrost core, we isolated eight genes conferring clinical levels of resistance against aminoglycoside, β-lactam and tetracycline antibiotics that are naturally produced by microorganisms. Among these resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
135
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(141 citation statements)
references
References 82 publications
4
135
0
2
Order By: Relevance
“…Detailed analysis of the vancomycin resistance gene cluster in this metagenome revealed conservation of gene sequence and synteny with modern resistance clusters in the clinic as well as protein function and structure. Other studies have shown the presence of resistance genes in Siberian permafrost (Petrova et al 2009) and showed working resistance genes from at least 5000 years ago using functional metagenomics (Perron et al 2015). Isolated instances of resistance genes in human commensals and pathogens have also been documented.…”
Section: Links To the Environment And Gene Mobilizationmentioning
confidence: 97%
See 1 more Smart Citation
“…Detailed analysis of the vancomycin resistance gene cluster in this metagenome revealed conservation of gene sequence and synteny with modern resistance clusters in the clinic as well as protein function and structure. Other studies have shown the presence of resistance genes in Siberian permafrost (Petrova et al 2009) and showed working resistance genes from at least 5000 years ago using functional metagenomics (Perron et al 2015). Isolated instances of resistance genes in human commensals and pathogens have also been documented.…”
Section: Links To the Environment And Gene Mobilizationmentioning
confidence: 97%
“…The DNA from permafrost can be isolated and queried experimentally for antibiotic resistance genes (among other things). The seminal work of D 'Costa et al (2011) on Beringian permafrost is complemented by studies showing that functional resistance genes can be retrieved from 5000-year-old DNA (Perron et al 2015), and that resistance had mobilized to plasmids and transposons in ancient times (Mindlin et al 2005;Petrova et al 2011Petrova et al , 2014. Modern day microorganisms found in a cave that has been isolated from the surface for four million years have also been shown to harbor functional antibiotic resistance genes (Bhullar et al 2012).…”
Section: Ancient Antibiotic Resistancementioning
confidence: 99%
“…Studies of extreme, polar environments characterized by a still limited anthropogenic influence (e.g., High Arctic or Antarctica) are of great importance, as they may reveal novel genes encoding heavy metal-resistance and metabolism mechanisms, and show the role of naturally occurring microorganisms in biogeochemical cycles. The results of several studies revealed that bacteria isolated from various Arctic and Antarctic environments show resistances to various toxic, antimicrobial agents, such as antibiotics and heavy metals (De Souza et al 2006Lo Giudice et al 2013;Mangano et al 2014;Moller et al 2014;Tomova et al 2014;Perron et al 2015;Rahman et al 2015;Tomova et al 2015;González-Aravena et al 2016;Rodriguez-Rojas et al 2016). However, overall knowledge on the resistome of polar bacteria is still rather limited, and the lack of a systematic approach, combining chemical, microbiological, and molecular analyses, is apparent.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial resistance to one or more antibiotics occurs by various mechanisms (24)(25)(26). In this way, EMFs as an environmental agent could influence cellular responses such as antimicrobial susceptibility through different pathways (4,20,22,23,27).…”
Section: Introductionmentioning
confidence: 99%